Infusion color and taste characteristic of Dafo Longjing tea processed from different cultivars - XU Pengcheng; FAN Fangyuan; LU Debiao; JIN jing; GONG Shuying (浙江大学学报. 农业与生命科学版, 2017)
Dafo Longjing tea, as one of top ten famous teas in Zhejiang Province, is mainly produced in Xinchang County and popular with consumers because of its fresh-tender aroma and soft-mellow taste. It is significantly different from other kinds of Longjing teas including famous Xihu- Longjing tea, and occupies large market share; however, studies on quality features and related components of Dafo Longjing tea are rather few at present. In order to delve deeply into the mechanism of quality formation of Dafo Longjing tea, systematic analyses of correlation between liquor-taste properties and chemical constituents were performed in this study.Dafo Longjing teas were processed by traditional processing procedure with fresh leaf from cultivars “Zhenong 113”, “Pingyang- tezao tea”, “Yingshuang”,“Longjing 43”, “Jiaming 1”, “Cuifeng”, “Baiye 1” and “Jiukeng”. The quality of the made teas was assessed by sensory evaluation, which showed that all of the samples made from different cultivars were accorded with the typical characteristic of flat, straight and bright appearance. The overall qualities of samples from “Longjing 43”, “Yingshuang” and “Jiaming 1” were superior to others, with the score of 94.80, 94.50 and 94.50 respectively. Characteristic constituents in tea samples were determined by high performance liquid chromatography. The result indicated that the “Jiukeng” and “Cuifeng” were with high content of catechins, and “Longjing 43” was with high content of gallic acid, and “Baiye 1” was with high content of amino acids. Flavonol glycosides, as essential functional ingredients with low content, were different in content among all the eight tea cultivars.As color indicators and representative of light- dark, red- green and yellow- blue degree respectively, values of L, a, and b were read to analyze the color difference of tea infusion. The result combined with sensory evaluation suggested that Dafo Longjing tea with high brightness and moderate yellow- green degree had good quality. What’s more, the result of tea infusion color difference analysis showed significant correlation with sensory evaluation, indicating that liquid quality of Dafo Longjing teas could be quantitative description by color indicators. Taken chemical determination together with color indicator analysis, we found that flavonol glycosides, especially myricetin glycosides and quercetin glycosides, had a significant impact on liquid color quality. Signal factor evaluation of taste characteristics could make sensory concept concretely and vividly, helping to understand product’s features. In this study, taste factors of umami, sweet, bitter, astringent and kokumi were scored by sensory experts. The result showed that bitter and astringent as important factors were speculated to have significant impact on taste quality of Dafo Longjing tea. In combination with quantitative analysis of chemical constituents, we found that flavonol glycosides were significantly correlated with taste factors of bitter, astringent and kokumi.Above all, color- indicator determination and signal factor evaluation can make sensory description of liquid and taste concretely and vividly. Moreover, flavonol glycosides as important chemical constituents have significant impact on liquid and taste quality, though with low content in Dafo Longjing tea. In the future, studies on the interaction between flavonol glycosides and other components will be explored further to illuminate the function mechanism of characteristic flavor.